Derivation of iPSC lines from two patients with autism spectrum disorder carrying NRXN1Î± deletion (NUIGi041-A, NUIG041-B; NUIGi045-A) and one sibling control (NUIGi042-A, NUIGi042-B) - Gallagher, Louise; Lynch, Sally (My University, 2021)
NRXN1 encodes thousands of splicing variants categorized into long NRXN1α, short NRXN1β and extremely short NRXN1γ, which exert differential roles in neuronal excitation/inhibition. NRXN1α deletions are common in autism spectrum disorder (ASD) and other neurodevelopmental/neuropsychiatric disorders. We derived induced pluripotent stem cells (iPSCs) from one sibling control and two ASD probands carrying NRXN1α+/-, using non-integrating Sendai viral method. All iPSCs highly expressed pluripotency markers and could be differentiated into ectodermal/mesodermal/endodermal cells. The genotype and karyotype of the iPSCs were validated by whole genome SNP array. The availability of the iPSCs offers an opportunity for understanding NRXN1α function in human neurons and in ASD.
PUBLISHED
cited By 0
Keywords: autism spectrum disorder (ASD); NRXN1 deletions; induced pluripotent stem cells (iPSCs); autism spectrum disorder (ASD); NRXN1 deletions; induced pluripotent stem cells (iPSCs)